Global renewal, religious pluralism, and the Great Commission: towards a renewal theology of mission and interreligious encounter - Yong, Amos; Clarke, Clifton (Asbury Theological Seminary series in Christian revitalization. Pentecostal / charismatic section, 2011)
This book explores the historical,theological and intercultural dimensions of these twin twentieth-century Restorationists traditions from a global perspective. In this volume Clifton Clarke and Amos Yong have edited essays that address the theological task of how an evangelistic theological tradition engages in authentic dialogue with non-Christian religions. Originally presented at a symposium held at Regent University, this volume breaks new ground as many of the leading global Pentecostal/Charismatic scholars addressing this issue were brought together to reflect upon this question. The results that emerge offer exciting possible trajectories as these persons join forces with scholars of other Christian traditions to engage in this significant dialogue of our time.